2016
DOI: 10.1163/15685322-10245p05
|View full text |Cite
|
Sign up to set email alerts
|

Buddhist Tales of Lü Dongbin

Abstract: During the early thirteenth century, a story began to appear within texts associated with the Chan 禪 Buddhist movement, which portrays an encounter between the eminent transcendent Lü Dongbin 呂洞賓 and the Chan monk Huanglong Huiji 黃龍誨機 that results in Lü abandoning his alchemical techniques of self-cultivation and taking up the practice of Chan. This article traces the development of this tale across a number of Buddhist sources of the late imperial period, and also examines the ways in which later Buddhist and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Farzeen Baldrian-Hussein (1986) has clarified some basic aspects about him in early legends that were created in the Northern Song dynasty, which were mainly hued with the color of Daoism. Other studies have, from different perspectives, showed that stories about Lü were tapped by other beliefs, for example, Buddhism (Capitanio 2016). Artistic and literary representations of Lü are so abundant and complex (as partly shown in (Katz 1999)) that the figure can be viewed as a cultural symbol for the expression of various ideas, mostly associated with religion and folk beliefs alike.…”
Section: Stories On Deities Delivering Willowsmentioning
confidence: 99%
“…Farzeen Baldrian-Hussein (1986) has clarified some basic aspects about him in early legends that were created in the Northern Song dynasty, which were mainly hued with the color of Daoism. Other studies have, from different perspectives, showed that stories about Lü were tapped by other beliefs, for example, Buddhism (Capitanio 2016). Artistic and literary representations of Lü are so abundant and complex (as partly shown in (Katz 1999)) that the figure can be viewed as a cultural symbol for the expression of various ideas, mostly associated with religion and folk beliefs alike.…”
Section: Stories On Deities Delivering Willowsmentioning
confidence: 99%